Makna Kata Rupa pada Ungkapan Paralel μορφῇ Θεοῦ dan μορφὴν δούλου dalam Filipi 2:6-7 - Andreas Kurniawan Purnomo; Ken Jacks Gunawan Waoma; Andreas Danang Rusmiyanto (Sekolah Tinggi Teologi Baptis, Jakarta, 2023)
This article discusses the many discussions regarding the nature of Jesus Christ and the circulation of false teachings regarding His divinity. This article discusses the meaning of the word like in the parallel expressions μορφῇ Θεοῦ (morphe Theou or the likeness of God) and μορφὴν δούλου (morphen doulou or the likeness of a servant) in Philippians 2:6-7. By conducting qualitative and hermeneutic research, this research aims to provide clear and relevant information for all believers today, which is often poorly understood by some people and groups. This word is often used to build the assumption that Jesus is only like or similar to God, but Jesus himself is not God. This view contradicts the Christian faith, which recognizes Jesus as God. This article presents a complete discussion regarding the meaning of the word μορφῇ (morphe or appearance) in the text Philippians 2:6-7. From the research results, it was found that the word